Load factors & service quality of the Berjaya Air schedule flight to Tioman / Lee Kuan Vu - Lee, Kuan Vu (1995)
This study is carried out to analyse the load factor and the quality of the schedule services to Tioman by Berjaya Air Sdn. Bhd. Load factors or loadings are very important in determining the number of passengers carried and the total passengers carried is the element of income for operating an air services. Service elements were identified as the quality which the company offer to the customer such as punctuality, frequency, reliability, comfortability and others. A survey was conducted to find out the customers' perception towards the service offered by Berjaya Air. The findings of the survey indicate that the passengers are satisfied with the overall service quality offered although there are some weaknesses that should be rectified by Berjaya Air in certain areas. Through improvement of efficiency and bigger aircraft in the operational side, the quality of service could be improved as well as the loading.